Effective adsorption and catalytic reduction of nitrophenols by amino-rich Cu(I)–I coordination polymer. (January 2023) - Hou, Jiayi; Si, Lin; Shi, Zekun; Miao, Chengxia; Zhao, Yan; Ji, Xiangshan; Hou, Qin; Ai, Shiyun
Abstract: Nitrophenols are identified as the priority organic pollutants due to the chemical stability, water solubility, persistence, and toxicity to human health and the environment. Hence, removal of nitrophenols from waste water is vitally essential. In this study, amino-rich coordination polymer Cu2 I2 (MA)2 (MA = melamine) has been applied for efficient adsorption and catalytic reduction of nitrophenols, like 4-nitrophenol (4-NP), 2, 4-dinitrophenol (DNP) and 2, 4, 6-trinitrophenol (TNP). The effect of various parameters like contact time, initial concentrations, pH, and temperature on adsorption were investigated. The adsorption of nitrophenols fitted the pseudo-second-order kinetic model and Langmuir isotherms model well. The maximum adsorption capacities were 285.71, 232.02, and 131.57 mg g −1 for 4-NP, DNP, and TNP when initial concentrations were 50 mg L −1 at 293.15 K, respectively. The adsorption of nitrophenols is a spontaneous, endothermic, and entropy-driven process. The reduction reaction followed the pseudo-first-order kinetics, and the kinetic rate constants were 0.4413, 0.3167, and 0.17538 min −1 for 4-NP, DNP, and TNP, respectively. The effect of initial nitrophenols concentration, anions, and temperature on reduction process was investigated. The mechanism of adsorption and catalytic reduction of Cu2 I2 (MA)2 was studied. The results demonstrated that Cu2 I2 (MA)2 exhibits excellent adsorption and catalytic activity to remove nitrophenols. Graphical abstract: Nitrophenols adsorption on Cu2 I2 (MA)2 by hydrogen bonding, electrostatic, electron donor-acceptor, π-π interaction, and electrons transfer from B H 4 − to nitrophenols then formation aromatic amines. Image 1 Highlights: Cu2 I2 (MA)2 exhibits effective adsorption and catalytic activity for nitrophenols. Effect of various factors on the adsorption and reduction were investigated. The adsorption and reduction mechanisms of nitrophenols for Cu2 I2 (MA)2 were analyzed. Adsorption is a monolayer, spontaneous, endothermic and entropy-driven process. The existence of Cu2 I2 (MA)2 promotes the formation of H radicals in reduction.